P3.07 Sexual profile and psychosocial aspects of a group of hiv infected women in rio de janeiro. (8th July 2017) - Helena, AAS; Ferreira, DC; Passos, MRL; Giesteira, AJ; Reis, HLB; Muchele, S; Peres, R
Abstract : Introduction: Women living with HIV have special features that arouse the interest of the scientific community, once they bring in themselves subjectivities that are beyond questions of clinical order. The objective of this study was to identify the patients' sexual and psychosocial profile of a public hospital in the state of Rio de Janeiro. Methods: A cross-sectional study and a semi structured interview with 70 HIV-infected women was carried out from April 2012 to March 2013. The patients were from an AIDS outpatient service of a hospital in Nova Iguaçu, in the State of Rio de Janeiro. Results: The average age of the participants was 34.9 years (SD =±11.2). More than half of women 55 (78.6%) acquired the infection through sexual intercourse. As for the marital status, 27 (38.6%) were single and 29 (41.4%) were married/stable union. 68 (97.2%) reported heterosexual orientation and 42 (60%) reported having active sexual life. Half of these women had occupation/employment, and few had already left the job because of infection, they reported that companies they worked at had no knowledge about the disease. The most common reasons cited were prejudice and by considering a matter of personal agenda. As for the self-perception, 38 (54.3%) of the evaluated women showed no satisfaction with their bodies, and 21 (30%) experienced a possible reduction of libido after infection. The use of HAART occurred in 51 (72.9%) patients, and even those classified as their biggest challenges in achieving treatment: adherence and access to the hospital, both with its implications. Conclusion: Our findings demonstrate the need to develop further health strategies in order to contribute to the comprehensive care that is being provided to these women, regarding their social reinsertion (occupation/employment), education, risk behaviour and preventive practices, serodiscordant relationships, disclosure, satisfaction with body and also the adherence to the proposed treatment.